A Student Walks into Class … Vignettes to Identify Substance Use Disorder Models of Illness among College Students. (24th August 2022) - Barry, Declan T.; Oberleitner, David E.; Beitel, Mark; Oberleitner, Lindsay M. S.; Gazzola, Marina Gaeta; Eller, Anthony; Madden, Lynn M.; Zheng, Xiaoying; Bergman, Emma; Tamberelli, Joseph F.
Abstract: Introduction: Illness models, including illness recognition, perceived severity, and perceived nature can affect treatment-seeking behaviors. Vignettes are a leading approach to examine models of illness but are understudied for substance use disorders (SUDs). We created vignettes for multiple common DSM-5 SUDs and assessed SUD illness models among college students. Methods: Seven vignettes in which the protagonist meets DSM-5 diagnostic criteria for SUDs involving tobacco, alcohol, cannabis, Adderall, cocaine, Vicodin, and heroin were pilot tested and randomly assigned to 216 college students who completed measures related to illness recognition, perceived severity, and perceived nature. MANOVAs with Scheffe post-hoc tests were conducted to examine vignette group differences on models of illness. Results: Vignettes met acceptable levels of clarity and plausibility. Participants characterized the protagonist's substance use as a problem, a SUD, or an addiction most frequently with Vicodin, heroin, and cocaine and least frequently with tobacco and cannabis. Participants assigned to the Vicodin, heroin, and cocaine vignettes were the most likely to view the protagonist's situation as serious and life-threatening, whereas those assigned to the cannabis vignette were the least likely. Numerically more participants characterized the pattern of substance use as a problem (91%) or an addiction (90%) than a SUD (76%), while only 15% characterized it as a chronic medical condition. Conclusions: Illness recognition and perceived severity varied across substances and were lowest for cannabis. Few participants conceptualized SUDs as chronic medical conditions. College students may benefit from psychoeducation regarding cannabis use disorder and the chronic medical condition model of SUDs.